Erros e obstáculos: os conteúdos matemáticos do ensino fundamental no processo de avaliação - MIRANDA, Werverton dos Santos (Universidade Federal do Pará, 2012)
This study presents a brief historical survey on the evaluation definition, teaching and learning obstacles - epistemological and didactic ones – as well as on the students’ errors. The three functions of the evaluation - diagnosis, formative and classificatory - are used in order to distinguish some negative and positive teaching practices in Mathematics. Concerning to the obstacles, specific literature points agreements related with their origin such as: epistemological, linguistics, emotional and didactics. From a historical point of view, the student errors leave a stigma of his/her ineptitude and incapacity. So, it is argued for a didactic instrument of assessment that can assist the students’ learning, in specially considering mathematical issues. The relations between error, evaluation or assessment and didactics obstacle is established to favor the possible contributions that the didactic identification of the errors and obstacles can offer to the improvement of the teaching-learning practice in Mathematics. On the other hand, a scientific study on the performance of the students at 5th to 8th grades was carried out, in Math. So an investigation was done to take in account some data collected from the answers given by four groups of students coming from Basic Education at a public school in Belem City/Para State/Brazil. To facilitate the fulfillment of the task proposal, it was defined as criteria for the analysis of the answers given by the students in some phased tests as the following: in the first one, the answers had been grouped in categories such as: questions without answers, incomplete, right and wrong and the way the subject suggests. In the second phase, the objective was to put in evidence the relations of concepts that contain expressed errors by the students and cause obstacles to learning or didactics obstacles. The results of this research point much more to the great percentage of error in the supposed concepts learned by those students in previous grades accented with what the subjects foreseen for the grade in which he/she is at present. It can be also noticed the great number of questions without answers, raising the suspicion of being one another indication of emerging didactics obstacles to be clarified and studied afterwards.